1960
DOI: 10.1111/j.1476-5381.1960.tb01227.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intracisternal Sarin and Pyridine‐2‐aldoxime Methyl Methanesulphonate in Anaesthetized Dogs

Abstract: Dogs poisoned by the anticholinesterase sarin could be saved by intravenous administration of atropine sulphate together with a suitable oxime. The central effects of intracisternal sarin were respiratory paralysis and vasomotor stimulation. The problem arose as to whether the oxime, being a quaternary nitrogen compound, could enter the brain from the blood, and could have a central action on the paralysed respiration. The methyl methanesulphonate of pyridine-2-aldoxime administered intracisternally, after sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The role of the latter, in reactivating inhibited cholinesterase, seems to be of prime importance in the periphery although statements (Brown, 1960;Hobbiger, 1963) that quatemary aldoximes do not penetrate into the central nervous system may have to be modified in view of more recent findings, for example those of Firemark, Barlow & Roth (1964), who showed that after large doses of labelled N-methylpyridinium-2-aldoxime it is possible to detect small amounts of the compound in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the latter, in reactivating inhibited cholinesterase, seems to be of prime importance in the periphery although statements (Brown, 1960;Hobbiger, 1963) that quatemary aldoximes do not penetrate into the central nervous system may have to be modified in view of more recent findings, for example those of Firemark, Barlow & Roth (1964), who showed that after large doses of labelled N-methylpyridinium-2-aldoxime it is possible to detect small amounts of the compound in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…This pressor response has been demonstrated with various OPs in humans (Holmes & Gaon, 1956), as well as in experimental animals (GB: Brown, 1960;Longo et al, 1960;DFP: Koppanyi et al, 1947Koppanyi & Karczmar, 1951), and~y various routes of administration including inhalation. Concomitant with the hypertensive response there is usually some bradycardia (Karczmar et al, 1966).…”
Section: Pharmacological Mechanisms and Contrihtitf!ig ~Actorsmentioning
confidence: 85%
“…One mechanism is a peripheral nicotinic pressor action demonstrated in the presence of atropine (Koppanyi et al, 1947(Koppanyi et al, , 1953Koppanyi & Karczmar, 1951). The second mechanism is-an-atropine-sensitive CNS pressor response demonstrated following intracerebroventricular injection of GD or GB (Brezenoff et al, 1984;Brown, 1960).…”
Section: Pharmacological Mechanisms and Contrihtitf!ig ~Actorsmentioning
confidence: 99%
“…By comparison of the illustrations in two of KoELLE's papers, it seems that P-2-AM is a more potent reactivator in vivo of AChE inhibited by DFP (KoELLE 1957) than is either MINA or DAM (RAJAPURKAR and KoELLE 1958). Although the quaternary oximes reactivate AChE in vivo in ganglia as well as in muscle (KOELLE 1957, RAJAPURKAR andKoELLE 1958) and in blood (HoBBIGER andSADLER 1959, WILLS 1959), they produce no significant reactivation of AChE in brain (HOBBIGER andSADLER 1959, WILLS 1959), nor do they antagonize significantly the toxic effects of anti-ChE agents on brain functions (SAKAI et al 1958, WILLS and BoRISON 1959, BRoWN 1960. This is true especially of the quaternized oximes; DAM in an i.v.…”
Section: G Chemicals That Prevent Ach Synthesis and Releasementioning
confidence: 93%